Dual Bandwidth Enhancement Using a New Multi-Resonance Feeding Structure for 5G Communication - Rui Li; Longyue Qu; Seokju Wi; Huanxuan Ren; Hyeongdong Kim (IEEE Access)
This paper introduces a multi-resonance feed structure to control the input impedance for achieving a dual wide-impedance bandwidth technology. According to the simulation, the bandwidth of the proposed antenna structure was approximately 330 MHz with the lower band (ranging from 670 MHz to 1000 MHz) and 1210 MHz with the higher band (ranging from 1670 MHz to 2880 MHz) under a 3:1 voltage standing wave ratio. Moreover, the average efficiency was significantly increased from 26.6% (reference) to 46.5% (proposed) at the lower band (ranging from 550 MHz to 1020 MHz) and even higher at the higher band, increasing from 15.5% (reference) to 61.2% (proposed) (ranging from 1400 MHz to 3000 MHz). The radiation pattern also showed satisfactory antenna radiation performance. This proposed technology has the advantage of achieving input impedance matching more easily and covers most fifth-generation (5G) NR operating bands in FR1 (n1, n3, n5, n8, n25, n30, n41, n66), indicating its promising application to 5G communication.